Student’s Social Moral in Adolescent Psychological Development - Ainissyifa, Hilda; Fauzi Ridwan, Fauzi (International Journal of Engineering and Technology, 2018)
Education in adolescence period is one of the important bases in students’ moral building. In education process, student’s behavior is allegedly influenced by the development of adolescent psychology. This study aims to reveal the influence of adolescent psychological development to student’s social moral. The method used in this research is a quantitative method with statistical descriptive and inferential approach. The research data are taken based on the occurring phenomenon and drawing conclusion from the data of sample result by t-test. This study involves 41 students as respondents, and the research site is Vocational School (SMK) of Al-Mukhtariyah, Cinisti Village, Bayongbong sub-district, Garut, Indonesia. The research finding showed that the variable reality of adolescent psychological development and students’ association moral are seen to have quite well criteria. The correlation between adolescent psychological development variable and students’ social moral is in the high category. According to the result of a significance test, the study stated that adolescent psychological development has significant positive effect on students’ social moral. The study recommends a holistic form of education, which does not only apply moral education at school. Moral education needs to get more attention from all parties such as school, society, parents, and government.